2021
DOI: 10.3390/agronomy11122479
|View full text |Cite
|
Sign up to set email alerts
|

Increased Number of Spikelets per Panicle Is the Main Factor in Higher Yield of Transplanted vs. Direct-Seeded Rice

Abstract: With increasing water shortages and labor costs, rice planting is gradually undergoing a transformation from traditional transplanting to direct seeding. However, the yield of direct-seeded rice is unstable and the reasons for this instability are disputed. Therefore, we established a field experiment conducted over 3 years to investigate the reasons for the difference in rice yield under different planting methods. The planting methods compared were transplanting (TR), broadcast sowing (BS), and sowing in lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 26 publications
2
5
0
Order By: Relevance
“…Number of panicles per unit area also showed similar trend as tiller number and it was found that number of panicles were more in DSR as compared to transplanting. Higher tiller number in DSR compared to transplanted rice was also observed in other studies (Mai et al, 2021). Xu et al, (2019) also reported positive response to direct rice seeding in terms of panicle number.…”
Section: Resultssupporting
confidence: 83%
“…Number of panicles per unit area also showed similar trend as tiller number and it was found that number of panicles were more in DSR as compared to transplanting. Higher tiller number in DSR compared to transplanted rice was also observed in other studies (Mai et al, 2021). Xu et al, (2019) also reported positive response to direct rice seeding in terms of panicle number.…”
Section: Resultssupporting
confidence: 83%
“…However, Qiqihar showed a higher number of productive tillers from each plant. These results are consistent with those reported by Kumar et al (2021) and Mai et al (2021), who reported that air temperatures <20 °C during the tillering phase were related to an increased number of panicles. Proportionately, the productive tillering capacity of a specific variety determines the overall yield potential; however, cultivars with more tillering capacity may exhibit a large repugnance in the transportation of assimilatory products and other essential nutrients, leading to major changes in grain development and, ultimately, grain yield and quality.…”
Section: Rice Quality In Inferior and Superior Grainssupporting
confidence: 93%
“…Longer panicles tend to increase the number of seeds per panicle, indicating a positive correlation between panicle length and seed yield (Mai et al, 2021). The Boyolali 200 Gy cultivar, specifically plant code M2-BY2-2-09, had the greatest seeds number per panicle, reaching 166.2 seeds (Table 4), although it was still lower than the control.…”
Section: Source: Laboratory Test Resultsmentioning
confidence: 94%